Dissolved Black Carbon in the Headwaters-to-Ocean Continuum of Paraíba Do Sul River, Brazil - Marques, Jomar S. J.; Dittmar, Thorsten; Niggemann, Jutta; Almeida, Marcelo G.; Gomez-Saez, Gonzalo V.; Rezende, Carlos E. (Frontiers in Earth Science, 2017)
Rivers annually carry 25-28 Tg carbon in the form of pyrogenic dissolved organic matter (dissolved black carbon, DBC) into the ocean, which is equivalent to about 10% of the entire riverine land-ocean flux of dissolved organic carbon (DOC). The objective of this study was to identify the main processes behind the release and turnover of DBC on a riverine catchment scale. As a model system, we chose the headwater-to-ocean continuum of Paraíba do Sul River (Brazil), the only river system with long-term DBC flux data available. The catchment was originally covered by Atlantic rain forest (mainly C3 plants) which was almost completely destroyed over the past centuries by slash-and-burn. As a result, large amounts of wood-derived charcoal reside in the soils. Today, fire-managed pasture and sugar cane (both dominated by C4 plants) cover most of the catchment area. Water samples were collected along the river, at the main tributaries, and also along the salinity gradient in the estuary and up to 35 km offshore during three different seasons. DBC was determined on a molecular level as benzenepolycarboxylic acids (BPCAs). Stable carbon isotopes (δ13C) were determined in solid phase extractable DOC (SPE-DOC) to distinguish C4 and C3 sources. Our results clearly show a relationship between hydrology and DBC concentrations in the river, with highest DBC concentrations and fluxes in the wet season (flux of 770 moles .sec 1 in 2013 and 59 moles .sec 1 in 2014) and lowest in the dry season (flux of 27 moles .sec 1). This relationship indicates that DBC is mainly mobilized from the upper soil horizons during heavy rainfalls. The relationship between DBC concentrations and δ13C-SPE-DOC indicated that most of DBC in the river system originated from C3 plants, i.e. from the historic burning event of the Atlantic rain forest. A conservative mixing model could largely reproduce the observed DBC fluxes within the catchment and the land to ocean continuum. Comparably slight deviations from conservative mixing were accompanied by changes in the molecular composition of DBC (i.e. the ratio of benzenepenta- to benzenehexacarboxylic acid) that are indicative for photodegradation of DBC.